Kebutuhan Bahan Ajar Sejarah Lokal di SMA - Krismawati, Nia Ulfia; Warto, Warto; Suryani, Nunuk (IAIN Ponorogo, 2018)
This study aimed to analyse the using of history textbook in the learning process, the role of history textbook to support the cultural literacy of local history, the local history literacy of students, and the need of teaching material that support the local history literacy. This research used qualitative method to get the qualitative data about the using history textbook and the cultural literacy of local history in SMAN 2 Ponorogo. The result showed that: (1) the history textbook that is used has not been supporting the cultural literacy of local history, (2) the cultural literacy of local history of students is in the low level, and (3) the students need a supplementary material of local history that allows them to do research and history writing integrated with the local history.ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙØÙÙÙ Ø¥Ø³ØªØ¹Ù Ø§ÙÙØªØ§Ø¨ Ø§ÙØªØ§Ø±ÙØ® ÙÙ Ø§ÙØªØ¹ÙÙÙ , ÙØ°Ø§ ÙØªØ§Ø¨ Ø§ÙØªØ§Ø±ÙØ® ÙØ³Ø§Ø¹Ø¯ Ø§ÙØªÙØ§Ù ÙØ° ÙÙ Ù Ø¹Ø±ÙØ© Ø§ÙØªØ§Ø±ÙØ® Ø§ÙÙ ÙØ¶Ø¹, Ø¥ÙÙ ÙØ¯Ø±Ø© Ø§ÙØªÙØ§Ù ÙØ° ÙÙ Ù Ø¹Ø±ÙØ© Ø§ÙØªØ§Ø±ÙØ® ÙÙ ÙÙØ¬ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØªØ§Ø±ÙØ® Ø§ÙÙ ÙØ¶Ø¹ ÙÙ ØªÙÙÙ Ø¬ÙÙØ¯Ø§. ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙØ³ØªØ¹Ù Ù Ø·Ø±ÙÙØ© Ø§ÙØ¨ØØ« Ø§ÙÙØ¶Ø¹, ÙÙÙÙ Ø§ÙÙÙ Ø¹ÙÙÙ Ø§Øª Ø§ÙØªÙ ØªØªØ¹ÙÙÙ ÙÙ Ø£Ù Ø± Ø§ÙÙØªØ§Ø¨ Ø§ÙØªØ§Ø±ÙØ® Ù ØØ§Ù Ù Ø¹Ø±ÙØ© Ø§ÙØªÙØ§Ù ÙØ° ÙÙ Ø£Ù Ø± Ø§ÙØªØ§Ø±ÙØ® Ø§ÙÙ ÙØ¶Ø¹ ÙÙ Ù Ø¯Ø±Ø³Ø© SMAN 2 Ponorogo . Ø§ÙÙØªÙØ¬Ø© Ù Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« ØªØ¹ÙÙ Ø£ÙÙ Ø§ÙÙØªØ§Ø¨ Ø§ÙØªØ§Ø±ÙØ® ÙÙ ÙÙÙ Ø¬ÙÙØ¯Ø§ ÙÙ Ø³Ø§Ø¹Ø¯Ø© Ø§ÙØªÙØ§Ù ÙØ° ÙÙÙÙ Ø§ÙØªØ§Ø±ÙØ® Ø§ÙÙ ÙØ¶Ø¹ Ø¨Ø¯ÙÙÙ Ø¥ÙÙ ÙÙÙ Ø§ÙØªÙØ§Ù ÙØ° ÙÙÂ Ø£Ù Ø± Ø§ÙØªØ§Ø±ÙØ®Â ÙØ¯Ø®Ù Ø¥ÙÙ Ø¯Ø±Ø¬Ø© Ø§ÙØ³ÙÙÙ. ÙØ§ÙØªÙØ§Ù Ù ÙØ° ÙØØªØ§Ø¬ÙÙ Ù ÙÙØ¬ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØªØ§Ø±ÙØ® Ø§ÙØ¬ÙÙØ¯Â Ø§ÙØ°Ù ÙØ³Ø§Ø¹Ø¯ÙÙ ÙÙ Ø§ÙØ¨ØØ« Ù Ø§ÙÙØªØ§Ø¨Ø© Ø§ÙØªØ§Ø±ÙØ® Ø§ÙÙ ÙØ¶Ø¹.